ANALISIS USER SATISFACTION TERHADAP VIRTUAL TOUR INTERAKTIF PADA CLUSTER D'ROYAL VILLAGE MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) TERINTEGRASI ISO/IEC 25010 - Ernisya Emilya; Faiza Rini; Rahayu Trisetyowati Untari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The development of digital technology encourages the use of virtual tours as an interactive promotional medium in the property sector. This study aims to analyze the level of user satisfaction with the web-based virtual tour at D'Royal Village using the System Usability Scale (SUS) method reinforced with usability aspects based on the ISO/IEC 25010 standard. The study used a descriptive quantitative approach with 30 respondents selected through purposive sampling. Data were collected using the SUS questionnaire and additional statements representing the sub-characteristics of appropriateness recognizability, user interface aesthetics, and operability. The results show an average SUS score of 77.50 (Acceptable, Grade B, "Excellent") and an ISO/IEC 25010 usability score of 76.25% (Good category). These findings indicate that the virtual tour has a good level of usability and is able to provide satisfaction to users, although the operability aspect still requires improvement to optimize the user experience. Keywords: Virtual Tour; User Satisfaction; Usability; Sus; ISO/IEC 25010 Abstrak: Perkembangan teknologi digital mendorong pemanfaatan virtual tour sebagai media promosi interaktif di sektor properti. Penelitian ini bertujuan menganalisis tingkat kepuasan pengguna terhadap virtual tour berbasis web pada D’Royal Village menggunakan metode System Usability Scale (SUS) yang diperkuat dengan aspek usability berdasarkan standar ISO/IEC 25010. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan 30 responden yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner SUS dan pernyataan tambahan yang merepresentasikan subkarakteristik appropriateness recognizability, user interface aesthetics, dan operability. Hasil menunjukkan skor rata-rata SUS sebesar 77,50 (Acceptable, Grade B, “Excellent”) dan skor usability ISO/IEC 25010 sebesar 76,25% (kategori Baik). Temuan ini mengindikasikan bahwa virtual tour memiliki tingkat usability yang baik dan mampu memberikan kepuasan kepada pengguna, meskipun aspek operability masih memerlukan peningkatan untuk mengoptimalkan pengalaman pengguna. Kata Kunci: Virtual Tour; User Satisfactio; Usability; SUS; ISO/IEC 25010